Theoretical study on a novel electromagnetically supported hydrodynamic bearing under static loads. (March 2018) - Goraj, Robert
Abstract: A novel hydrodynamic plain journal bearing is presented, in which the thickness of the lubricant is simultaneously used as an airgap of the electromagnetic system. The bearing combines the advantages of hydrodynamic and magnetic bearings, and can be manufactured as one coherent unit. This paper develops a new governing equation system describing stationary loci of such an electromagnetically supported short hydrodynamic plain journal bearing under hydrodynamic, electromagnetic and gravity forces. The derived ordinary equation system describing an implicit equilibrium position of the bearing is solved semi-analytically for different hydrodynamic and electromagnetic loads to provide equilibrium loci. This solution is subsequently verified by means of the Finite Difference Method. Graphical abstract: Highlights: A novel electromagnetically supported hydrodynamic bearing: technical and physical background, functionally and expected advantages of. Introduction of a new number Vo, similarly constructed to the Sommerfeld number So . Elaboration of a new governing equation system describing a position of rest (an equilibrium locus) of the novel journal bearing. Both semi-analytical and numerical estimation of equilibrium loci.